Factors Predicting the Adherence to the Therapy of Italian IBD Patients - Cristina Bucci; Fabiana Zingone; Stella Tammaro; Paola Iovino; Antonella Santonicola; Carolina Ciacci (Gastroenterology Research and Practice)
Background. Inflammatory bowel diseases (IBD) are chronic gastrointestinal disorders influencing many aspects of the patient’s life and accounting for substantial social costs. They require long-term therapies and regular contact with the clinic of reference. Our aim is to investigate therapy adherence and identify predictors of adherence. Methods. 151 patients were recruited in IBD clinic at the University of Salerno filled in the modified Morisky Medication Adherence Scale, a standardized questionnaire provided during the visit. Results. Overall, 71.5% of the patients report to take all medications regularly. According to the scale, our population showed a 62.5% medium-high adherence to oral 5-ASA, a 72% medium–high adherence to immunomodulators, a 60% medium–high adherence to oral steroids, and 94.9% adherence to biologics. Younger patients tend to be less compliant to the therapy. The main reasons for the low adherence to therapy were the “hassle of sticking to the medication plan” and “their feeling better.” Conclusion. In Italy, where the healthcare system covers most of the expenses for IBD therapy, almost 30% of IBD patients report low compliance to therapy. Healthcare givers should improve the knowledge regarding the disease and favor the development of combined drugs that would simplify the daily medication plan.